The Quality of Mathematics Teaching Aids Developed by Mathematics Pre-Service Teachers in Indonesia - Naufal Ishartono; Ikhsan Dwi Setyono; Ade Risma Maharani; Suliadi Firdaus Bin Sufahani (Jurnal VARIDIKA, 2022)
Mathematics teaching aids play an essential role in the learning process, where these aids become a bridge in the transfer of knowledge between teachers and students. The good of mathematics learning media will affect the process of transfer of knowledge from teacher to student. Therefore, this study aims to analyze and describe the quality of mathematics teaching aids developed by pre-service mathematics teachers in Indonesia, specifically from pre-service mathematics teachers in the Mathematics Education Department of Universitas Muhammadiyah Surakarta. This study uses descriptive analytical studies in which the data obtained is analyzed quantitatively and described qualitatively. This study concludes that, in general, the quality of mathematical teaching aids developed has been categorized as at least "good enough" both in pedagogical and conceptual aspects, as well as in physical aspects. However, some points need notable improvement and attention by the teaching lecturers at the point of the level of quality of safety and the quality of the teaching's ability aids in providing stimulus to students.